Analisis dan Perancangan Sistem Informasi Akuntansi Industri Kecil Menengah (SIA-IKM) Menuju Masyarakat Ekonomi Kreatif - Wiwit Irawati; Luh Nadi; Harry Barli (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2021)
ABSTRACTThis research is motivated by the importance of SMIs using the Accounting Information System which will help SMIs produce reports that can be used both for external parties and as a tool in making decisions for the IKM itself so that the effectiveness and operational efficiency of the entity can be improved. This will make IKM able to compete and develop which means empowerment of the creative economy to achieve its goals. This study took the IKM population in South Tangerang, and the sample was selected using the convenience sampling technique. Before being processed using the SPSS program, the data in the form of recapitulated questionnaires were tested for validity and reliability, tested classical assumptions, then tested the partial hypothesis (t). The results showed that the Financial Position Reporting System affected the Empowerment of the Creative Economy, as well as the Finished Goods Inventory System, while the Raw Material Inventory System and the Profit / Loss Reporting System did not affect the Empowerment of the Creative Economy.